Association of ERAP1 and ERAP2 gene polymorphisms and ERAP2 protein with the susceptibility and severity of rheumatoid arthritis in the Ukrainian population - Kril, Iryna; Wiśniewski, Andrzej; Tarnowska, Agnieszka; Lishchuk-Yakymovych, Khrystyna; Bojko, Yaryna; Kuśnierczyk, Piotr; Chopyak, Valentyna V.; Nowak, Izabela (Frontiers in Immunology, 2025)
IntroductionRheumatoid arthritis (RA) is a long-term autoimmune disorder that primarily affects joints. Although RA is chiefly associated with HLA class II, nevertheless some HLA class I associations have also been observed. These molecules present antigenic peptides to CD8+ T lymphocytes and natural killer cells. HLA-I molecules bind their peptide cargo (8–10 amino acids long) in the endoplasmic reticulum. Peptides longer than 10 amino acids are trimmed by the endoplasmic reticulum aminopeptidases ERAP1 and ERAP2 to fit the peptide binding groove of the HLA-I molecule. Here, we investigated the possible association of ERAP1 and ERAP2 polymorphisms with RA, and also any possible correlation between serum levels of the ERAP2 protein with disease severity.MethodsWe used Real-Time PCR to genotype ERAP1 and ERAP2 and ELISA test to detect ERAP2 protein.ResultsWe found significant associations of ERAP1 rs30187, rs27044, and rs26618, as well as ERAP2 rs2248374, with susceptibility to RA. ERAP1 rs26653 and ERAP2 rs2248374 were also associated with the Disease Activity Score (DAS28), and some polymorphisms were also associated with anti-citrullinated protein or anti-mutated citrullinated vimentin antibodies. RA patients secreted higher concentrations of ERAP2 than controls. Patients with mild disease activity (DAS28 < 3.2) released a concentration of ERAP2 four times lower than that of patients with severe disease activity (DAS28 > 5.1). We detected a higher level of ERAP2 in rheumatoid factor (RF)-positive patients than in RF-negative patients. ERAP2 concentration above 5.85 ng/mL indicated a severe phase of RA.ConclusionsSome ERAP1 and ERAP2 polymorphisms seem to be related to susceptibility to RA or the severity of the disease. The ERAP2 protein tested in serum could be a valuable biomarker of RA severity.